Purchase Behavior and Service Marketing Mix Influencing Consumers' Repurchase Intention toward Community Grocery Retail Stores - chutima wangbenmad; Thitikarn Sirican (AMAR (Andalas Management Review), 2026)
This study examined consumers' purchase behavior and investigated the influence of the Service Marketing Mix (7Ps) on repurchase intention toward community grocery retail stores. A quantitative research design was employed, with data collected from 178 consumers who had experience purchasing products from community grocery retail stores. Multiple regression analysis was used to examine the relationships among variables. The results revealed that most consumers purchased products 2–3 times per week, preferred shopping after work, made purchasing decisions independently, selected stores located close to home, and paid via bank transfer or PromptPay. Regarding the Service Marketing Mix, Place ranked highest in importance, followed by People and Process, respectively. The regression analysis found that Process (β = .354), Place (β = .313), and People (β = .187) significantly influenced consumers' repurchase intention, collectively explaining 69.5% of the variance (R² = .695). In contrast, Product, Price, Promotion, and Physical Evidence did not have statistically significant effects. These findings suggest that efficient service delivery, convenient accessibility, and positive interpersonal relationships are the primary drivers of repeat purchasing behavior in community grocery retail contexts. Community retail store operators are recommended to prioritize service process improvement, location convenience, and customer relationship development to enhance customer retention and long-term business sustainability.